O que dizem os professores das 4as séries do ensino fundamental sobre o ensino de ciências neste nível de escolaridade - Guzzi, Igor de Souza (2006)
More and more, the society has required citizens to act in a world which scientific and technology knowledge is extremely worth. The evolution of these knowledges works as a modern world´s mirror, which, indeed, reflects all the progress that conduced to the development of the actual society, consisted by the amazing velocity the information is spread, and by the incredible science dynamism. In this way, make people get closer from informations about science takes an important and challengeable role. Important since it leads you to a world comprehension and its information; challengeable because of the complexity that involves the teaching and learning task. The science studies has to act as a contributor to the reality comprehension, mainly in understanding the natural events, stimulating questions about the differents ways the interventions can modify them. In that case, the investigation of the questions that covers the learning process of teaching modality since basic grades becomes indispensable, as we think about the developments coming from critical people who are acting directly on the society. The main purpose of the present work was to obtain elements that could bring possibilities of proofs, reflections and discussions around the science teaching in basic grades, especially on the fourth grade, which is the focus of this research. For that, it was necessary an approximation to science teaching history and to the different sources teachers acquire to be able to get the knowledges which state their praticals, involving questions about the science curriculum, materials used within the classes and others aspects that leaded to a bigger approximation to the process of teaching and learning. The investigation started from a theoretical reference based on teacher s knowledges. Therefore, a better comprehension of how teachers relate with the knowledges that are used within their science classes and how those knowledges are acquired were better understood.